Proliferation inhibition of novel diphenylamine derivatives - Janovec, Ladislav; Janočková, Jana; Matejová, Mária; Konkoľová, Eva; Paulíková, Helena; Lichancová, Daniela; Júnošová, Lenka; Hamuľaková, Slávka; Imrich, Ján; Kožurková, Mária (Bioorganic chemistry, 2019)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most widely used drugs in the world but some NSAIDs such as diclofenac and tolfenamic acid display levels of cytotoxicity, an effect which has been attributed to the presence of diphenylamine contained in their structures. A novel series of diphenylamine derivatives were synthetised and evaluated for their cytotoxic activities and proliferation inhibition. The most active compounds in the cytotoxicity tests were derivative 6g with an IC50 value of 2.5 ± 1.1 × 10-6 M and derivative 6f with an IC50 value of 6.0 ± 3.0 × 10-6 M (L1210 cell line) after 48 h incubation. The results demonstrate that leukemic L1210 cells were much more sensitive to compounds 6f and 6g than the HEK293T cells (IC50 = 35 × 10-6 M for 6f and IC50 > 50 × 10-6 M for 6g) and NIH-3T3 (IC50 > 50 × 10-6 M for both derivatives). The IC50 values show that these substances may selectively kill leukemic cells over non-cancer cells. Cell cycle analysis revealed that a primary trend of the diphenylamine derivatives was to arrest the cells in the G1-phase of the cell cycle within the first 24 h. UV-visible, fluorescence spectroscopy and circular dichroism were used in order to study the binding mode of the novel compounds with DNA. The binding constants determined by UV-visible spectroscopy were found to be in the range of 2.1-8.7 × 104 M-1. We suggest that the observed trend for binding constant K is likely to be a result of different binding thermodynamics accompanying the formation of the complexes.
Keywords: G1 Phase Cell Cycle Checkpoints; DNA minor groove binder; Humans; simulace molekulového dockingu; Benzimidazoles; termodynamika; Molecular Docking Simulation; Antineoplastic Agents; difenylamin; lidé; kontrolní body fáze G1 buněčného cyklu; HEK293 Cells; zvířata; proliferace buněk; myši; buňky NIH 3T3; benzimidazoly; Intercalating Agents; Mice; DNA; simulace molekulární dynamiky; interkalátory; Diphenylamine; NIH 3T3 Cells; fluorescenční barviva; Thermodynamics; Antiproliferative; Fluorescent Dyes; Molecular Dynamics Simulation; HEK293 buňky; Cell Proliferation; nádorové buněčné linie; protinádorové látky; DNA binding study; Animals; Cell Line, Tumor